An electrophysiological investigation into ‘Bagels’: a song recorded to reduce subclinical anxiety in youth - Shepherd, Daniel; Pedersen, Mangor; Vashista, Geet; Kercher, Amy; Hautus, Michael J. (Frontiers in Neuroscience, 2025)
IntroductionReceptive Music Therapy allows individuals with sub-clinical anxiety levels to self-medicate when and where they choose, but the effectiveness of self-administered ‘music medicine’ to enhance psychological well-being is still being investigated. The current study reports on a song (‘Bagels’) designed to alleviate mild anxiety in adolescents and young adults.MethodsA laboratory study was conducted to examine the effect of Bagels on brain states, and upon both subjective and objective measures of state anxiety. Measures of skin conductance and heart rate (HR), and 64-channel Electroencephalography (EEG) were obtained from 30 young adults as they listened to six songs contrasting affective properties. Subjective measures included ratings of a song’s pleasantness, arousal, dominance, and likability, as well as estimates of state anxiety obtained immediately after listening to them.ResultsPreliminary analyses revealed that the six songs differed significantly in terms of affective ratings, with Bagels rated as more pleasant and less arousing, and having lower state anxiety ratings at its terminus. EEG alpha connectivity was also lowest for the song Bagels, particularly in the brain’s frontal lobes. Similarly, Bagels was associated with lower physiological arousal, reflecting less arousal and greater calmness.DiscussionCombined, the analysis suggest that Bagels has the potential to be an effective digital anxiolytic. Discussion around the promise of music medicine and aspects of its management are presented, along with avenues of further inquiry.